Reply to Comment on "An Unusual Case of Acquired Angioedema and Monoclonal Gammopathy of Renal Significance in a Middle-Aged Caucasian Female" - Sasmit Roy MD; Venu Madhav Konala MD; Thurein Kyaw MD; Sandipan Chakraborty MD; Srikanth Naramala MD; Vijay Gayam MD; Sreedhar Adapa MD; Subhasish Bose MD (SAGE Publishing, 2020)
We sincerely thank Dr Andrew Whyte, who keenly reviewed our case report and came up with critical reasoning to justify his thoughts and critique with regard to our published article, "An Unusual Case of Acquired Angioedema and Monoclonal Gammopathy of Renal Significance in a Middle-Aged Caucasian Female." We agree with the author that hypocomplementemic urticarial vasculitis can be a reasonable contender as a diagnosis in this case. There are indeed some features in this case that do not entirely fit either classic presentation of acquired angioedema or hypocomplementemic urticarial vasculitis. Both diseases being equally rare, we tried to focus on the association of proliferative glomerulonephritis with angioedema-like features in this patient and considered acquired angioedema as the unifying diagnosis.